The role of job stress as a mediator on toxic leadership and turnover intention in Gen Z employees - Minarti, Kurnianingrum Ayu; Zamralita, Zamralita (Jurnal Psikologi Terapan dan Pendidikan, 2025)
Turnover intention is a pressing concern for organizations, as employees are increasingly choosing to leave due to toxic leadership. Toxic leaders characterized by intimidation, manipulation, and a lack of support create detrimental work environments that elevate employee stress levels. This heightened stress, in turn, intensifies turnover intention, leading to higher retention rates. Toxic leadership not only undermines employee well-being but also significantly impairs organizational performance. This study aims to investigate the impact of toxic leadership on turnover intention, with job stress acting as a mediating variable. Focusing on Generation Z employees a growing segment of the workforce demographic this research examines how the unique challenges of this group interact with toxic leadership, offering crucial insights for organizations. The study employs a quantitative research approach utilizing survey methodology. Data were collected through questionnaires by involving 400 Generation Z employees in Jakarta. The sampling technique used was convenience sampling. The study utilized the Toxic Leadership Scale, Intention to Leave Scale, and Job Stress Scale as instruments. The results demonstrated that toxic leadership significantly drives turnover intention, with job stress playing a key mediating role. Toxic leadership was found to increase job stress, which, in turn, strengthened the intention of Generation Z employees to leave their jobs. These findings underscore the pressing need for organizations to address toxic leadership, thereby enhancing employee well-being and reducing turnover rates. The study offers valuable insights for organizations seeking to foster a healthier work environment and enhance employee retention.